Levobupivacaine versus ropivacaine for brachial plexus block: A systematic review and meta-analysis of randomised controlled trials - Abdullah M. Alharran; Muteb N. Alotaibi; Yaqoub Y. Alenezi; Yousef M. Alharran; Ahmad A. Alahmad; Abdulmuhsen Alqallaf; Mohammad F. Al-Mutairi; Abdulbadih R. Saad; Mohammed H. Alazemi; Duaij S. Saif; Ebraheem Albazee; Ahmad Y. Almohammad (Indian Journal of Anaesthesia)
Background and Aims: Brachial plexus block (BPB) is advantageous for elective orthopaedic or reconstructive upper limb surgery. However, the optimal local anaesthetic in BPB remains debatable. Therefore, we aim to investigate the efficacy and safety of levobupivacaine versus ropivacaine in BPB for upper limb surgery. Methods: A systematic review and meta-analysis synthesising randomised controlled trials (RCTs), retrieved by systematically searching PubMed, EMBASE, WOS, SCOPUS, Google Scholar, and CENTRAL since inception till June 2024. Continuous and dichotomous outcome variables were pooled using mean difference (MD) and risk ratio (RR), with a 95% confidence interval (CI), using Stata v. 17. We assessed heterogeneity using the Chi-square test and I2 statistic. Results: Sixteen RCTs and 939 patients were included. Levobupivacaine was significantly associated with a longer sensory block duration [MD: 1.66 (95% CI: 1.43, 1.89), P < 0.001] and motor block duration [MD: 1.18 (95% CI: 0.11, 2.26), P = 0.03]. However, there was no difference between both groups in time to sensory block [MD: −0.30 (95% CI: −1.31, 0.71), P = 0.56], time to motor block [MD: −0.29 (95% CI: −1.26, 0.67), P = 0.55], pain score [MD: −0.48 (95% CI: −2.13, 1.16), P = 0.56], rescue analgesia rate [RR: 0.94 (95% CI: 0.74, 1.20), P = 0.64], and complications [RR: 0.47 (95% CI: 0.20, 1.13), P = 0.09]. Conclusions: Levobupivacaine is significantly associated with a longer duration of sensory and motor block in patients undergoing BPB for upper limb surgery compared to ropivacaine, with a similar safety profile. However, there was no difference regarding the time to onset of the sensory or motor block.